2004
DOI: 10.1113/jphysiol.2003.055053
|View full text |Cite
|
Sign up to set email alerts
|

A reduced cerebral metabolic ratio in exercise reflects metabolism and not accumulation of lactate within the human brain

Abstract: During maximal exercise lactate taken up by the human brain contributes to reduce the cerebral metabolic ratio, O 2 /(glucose + 1/2 lactate), but it is not known whether the lactate is metabolized or if it accumulates in a distribution volume. In one experiment the cerebral arterio-venous differences (AV) for O 2 , glucose (glc) and lactate (lac) were evaluated in nine healthy subjects at rest and during and after exercise to exhaustion. The cerebrospinal fluid (CSF) was drained through a lumbar puncture immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
188
0
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(194 citation statements)
references
References 46 publications
(66 reference statements)
3
188
0
3
Order By: Relevance
“…This evidence should at least raise some doubt regarding the notion that lactate is a dead-end product. Moreover, a recent human study by Dalsgaard et al (2004) has indicated that lactate, produced during exercise, is taken up and metabolized by the brain. Nevertheless, the widely accepted dogma that, aerobically, pyruvate, not lactate, is the final product of glycolysis (reaction II) is both chemically and thermodynamically flawed.…”
Section: Background Considerationsmentioning
confidence: 99%
“…This evidence should at least raise some doubt regarding the notion that lactate is a dead-end product. Moreover, a recent human study by Dalsgaard et al (2004) has indicated that lactate, produced during exercise, is taken up and metabolized by the brain. Nevertheless, the widely accepted dogma that, aerobically, pyruvate, not lactate, is the final product of glycolysis (reaction II) is both chemically and thermodynamically flawed.…”
Section: Background Considerationsmentioning
confidence: 99%
“…Lactate is cotransported with one H + (Becker et al, 2004;Juel, 2001) and, at any given lactate concentration, the H + (or pH) gradient between blood and brain influences lactate transport, as illustrated by an increased lactate uptake when pH becomes low (Oldendorf et al, 1979). Often even maximal exercise elicits, but a small decrease in pH (Dalsgaard et al, 2002(Dalsgaard et al, , 2004c). Yet, in a competitive setting such as elite rowing blood pH may decrease to as low as B6.8, with blood lactate increasing up to B30 mmol/L (Nielsen, 1999).…”
Section: Lactatementioning
confidence: 99%
“…(reviewed in Gladden, 2004;Hertz and Dienel, 2005;Pierre and Pellerin, 2005). As transport is down the concentration gradient, a significant lactate uptake requires that the arterial level exceeds that within the brain of B1.5 mmol/L (Abi-Saab et al, 2002;Dalsgaard et al, 2004c) ( Table 1). Thus, from an arterial lactate concentration < 1 mmol/L in a physically inactive subject, a several fold increase in the arterial concentration, as during strenuous exercise, is required to accelerate transport.…”
Section: Lactatementioning
confidence: 99%
“…It has previously been demonstrated lactate cannot easily cross the bloodbrain barrier (Hertz andDienel, 2002 andAuer, 1986), infusing lactate intravenously does not increase CSF lactate (Alexander et al, 1962) and levels of blood and CSF lactate are regulated independently (Posner and Plum, 1967). However, others have documented that the blood-brain barrier is permeable to lactate (Dalsgaard et al, 2004, Smith et al, 2003and Oldendorf, 1973 and the lactate transporter MCT1 is expressed on endothelial cells (Gerhart et al, 1997). Furthermore, Tofteng and Larsen (2002) in a case report describing a patient with severe ALF and brain edema found microdialysate (extracellular) lactate was influenced by alterations in arterial concentrations of lactate.…”
Section: From the Bloodmentioning
confidence: 99%